2000
DOI: 10.1016/s0925-4773(00)00262-8
|View full text |Cite
|
Sign up to set email alerts
|

Androcam, a Drosophila calmodulin-related protein, is expressed specifically in the testis and decorates loop kl-3 of the Y chromosome

Abstract: The Drosophila genome encodes a protein that is 68% identical to Drosophila calmodulin (Cam). We show here that this Cam-related gene is specifically expressed in the germ-line of the testis, leading to the name Androcam (Acam). Early in spermatogenesis Acam accumulates on one of the chromatin loops of the Y chromosome, kl-3. This association with kl-3 may indicate an RNA processing-related role for Acam and/or could reflect an unusual storage/assembly function hypothesized for the Y loops. After meiosis Acam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
0
14
1
Order By: Relevance
“…Neither of the Drosophila CaM antibodies used previously for immunolocalization studies in other tissues (32) revealed specific staining for CaM on the actin cone fronts (22). Furthermore, immunoprecipitation experiments presented here showed that while CaM could be found in a complex with myosin VI in ovarian extracts, such an interaction was not detectable in testis extracts.…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…Neither of the Drosophila CaM antibodies used previously for immunolocalization studies in other tissues (32) revealed specific staining for CaM on the actin cone fronts (22). Furthermore, immunoprecipitation experiments presented here showed that while CaM could be found in a complex with myosin VI in ovarian extracts, such an interaction was not detectable in testis extracts.…”
Section: Discussioncontrasting
confidence: 74%
“…We co-labeled wild-type testes with antibodies specific for myosin VI and Acam. The Acam antibody used, RU158, has a ϳ100-fold higher specificity for Acam than CaM (22). We found that in individualizing spermatids, myosin VI and Acam showed perfect co-localization in a series of discrete, tight bands (Fig.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations